Efficacy and tolerability of preservative-free tafluprost 0.0015% in Korean patients with glaucoma - Hwang YH (Dove Medical Press, 2013)
Young Hoon HwangDepartment of Ophthalmology, Konyang University, Kim's Eye Hospital, Myung-Gok Eye Research Institute, Seoul, KoreaI read with interest the article entitled "Preservative-free tafluprost in the treatment of naive patients with glaucoma and ocular hypertension" by Lanzl et al.1 I have also experienced similar treatment outcomes in Korean patients. In Korea, preservative-free tafluprost (Taflotan-S; Santen Pharmaceutical Co, Ltd, Osaka, Japan) was introduced to the ophthalmic market in October 2012. Thus far, no data have been published on the efficacy and tolerability of preservative-free tafluprost in Korean patients. Thus, I investigated the intraocular pressure (IOP)-lowering efficacy and safety of preservative-free tafluprost in treatment-naïve Korean patients with glaucoma.View original paper by Lanzl and colleagues.